Energy generation and efficiency technologies for green residential buildings - Ting, David S-K; Carriveau, Rupp (Institution of Engineering and Technology, 2019)
The book comprises of 11 chapters and studies the energy generation and efficiency technologies for green residential buildings. Areas covered include: clean energy generation; photovoltaic arrays; PV solar systems; solar energy generation technology; phase change materials; energy efficiency; secondary battery technologies; solar radiation analysis and nature-based building solutions.
Keywords: Buildings -- Energy conservation.; Energy consumption.; Green technology.; Sustainable living.; elektronické knihy; electronic books